(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2023)
The article addresses the language used in relation to pupils with Asperger syndrome at Polish schools. It is based on the conclusions from the analysis of interviews conducted with parents of children on the autism spectrum in two periods: in 2015–2020 (32 interviews conducted in person) and in 2022 (43 interviews conducted online). The results of the study show that numerous terms are used at schools with respect to pupils with Asperger’s syndrome that have an exclusionary, stigmatising and sometimes even vulgar nature. Unfortunately, such exclusionary language is often used not only by those pupils’ peers, but also by their teachers.